PRIME LENDING RATE AND BANK PERFORMANCE: EVALUATION OF CREDIT QUALITY IN EMERGING COUNTRY - Karim, Muhammad; Novitasari, Desi; Valdiansyah, Riyan Harbi; Lorensa, Roro Lonita (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
This study investigates the impact of the prime lending rate on credit quality and its subsequent effect on banking performance (LDR, ROA, NIM) in Indonesia. This quantitative study encompasses 43 conventional banks listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023, with 215 data points. The originality of this study lies in its examination of the direct and indirect effects of credit quality on the relationship between the prime lending rate and banking performance. The data were analyzed using the mediation regression method with panel data, using EViews 13.0 employed for this purpose. The results of the study demonstrate that PLR has a positive effect on credit quality (NPL) and LDR, but a negative effect on ROA, and no effect on NIM. Conversely, NPL exerts a negative influence on LDR, ROA, and NIM. The mediation test revealed that PLR has a negative effect on LDR, ROA, and NIM through NPL. Ultimately, the findings suggest that banking practitioners should exercise caution when pursuing high net interest margin (NIM), return on assets (ROA), and loan-to-deposit (LDR) ratios. Instead, a more prudent approach to extending credit is recommended to maintain the NPL ratio below 5%. This approach contributes to the sustained financial stability of the banking institutions under consideration. For policymakers, the study offers insights into the broader effects of interest rate changes on banking stability and credit quality in emerging markets. Financial regulators, such as Bank Indonesia, could utilize these findings to develop policies that balance economic growth objectives with financial stability. For instance, they could implement measures to maintain NPLs below critical thresholds during periods of fluctuating interest rates. These implications encourage a balanced approach to managing interest rates, focusing on credit quality, and maintaining consistent performance to ensure long-term financial stability.